Safety of a physical therapy protocol for women with preeclampsia: a randomized controlled feasibility trial - Tawana Vicente Bertagnolli; Michelle de Souza Rangel Machado; Cristine Jorge Homsi Ferreira; Jackeline de Souza Rangel Machado; Geraldo Duarte; Ricardo Carvalho Cavalli (Taylor & Francis Group, 2018)
Objective: To assess the feasibility and safety of a physiotherapy protocol applied to pregnant women with preeclampsia. Methods: Randomized, controlled, single-blind feasibility study, with 24 hospitalized pregnant women with preeclampsia. The intervention group received one session of the physiotherapy. The control group remained under the routine care of the hospital. The primary outcomes were Doppler velocimetry, cardiotocography, and maternal-fetal hemodynamics. Secondary outcomes were pain and anxiety assessed before and after the interventions. A mixed effects linear regression model was used, and the data were compared with the level of significance at 5%. Results: The baseline characteristics of the participants were homogeneous between groups. Resistance index of the Middle Cerebral Artery (MAC) and Umbilical Artery (UA) and cardiotocography did not change significantly. The systolic blood pressure (SBP) increased 4.90 mmHg in the control group and 0.22 mmHg in the intervention group. The diastolic blood pressure (DBP) increased 1.34 mmHg in the control group and decreased 0.40 mmHg in the intervention group. The middle bood pressure (MBP) increased 4.66 mmHg in the control group while there was a decrease of 0.09 mmHg in the intervention group, without statistical difference. Heart rate (HR) decreased 0.94 bpm in the control group; whereas, in the intervention group, there was an increase of 6.30 bpm. The pain reduced clinically 2 points after the intervention. The anxiety reduced clinically in both the groups (−1.26 in the intervention group and −2.17 in the control group). Conclusion: The protocol applied in the intervention group is feasible and safe for both mother and fetus. Both groups showed clinical reduction in the levels of anxiety; whereas, pain was clinically reduced in the intervention group.